Anti-corruption and disclosure ownership structure of company value using risk as an intervening variable - Valentina, Refina Shinta (Sebelas Maret Business Review, 2022)
This research was conducted to determine the effect of anti-corruption disclosure on company value through risk as an intervening variable. Employing secondary data obtained from annual financial report data, Corporate Social Responsibility reports, and sustainability reports of mining companies listed on the Indonesian stock exchange, this research produced 56 samples during 2019, with a total of 73 populations using a purposive sampling technique. Companies in Indonesia have an average high company value, so the public's view of the company's welfare is also high. However, there are several companies whose share prices could be more stable. The analysis technique in this study uses Smart PLS. Descriptive analysis and statistics reveal that anti-corruption disclosure and ownership structure have no significant effect on the risk and value of the company. However, trouble has a substantial impact on company value. This research provides several suggestions to increase company value. Companies should publish complete financial reports accompanied by CSR reports and sustainability reports, make anti-corruption commitments, pay attention to risk, and manage the ownership structure by using domestic ownership at a certain level. For investors, it is better to diversify your investment by investing in an optimal portfolio of several profitable stocks.